Risk stratification for decision-making in myocardial revascularization - Custodio-Sánchez, Piero (2019)
Chronic coronary artery disease is a leading cause of mortality worldwide. Myocardial revascularization, through percutaneous coronary intervention or coronary artery bypass grafting, is a mainstay in the treatment, and the decision between their must be made by a multidisciplinary team that considers the risks and benefits inherent to each one. Several prognostic scores, with advantages and limitations, are used in clinical practice. The purpose of this review is to provide information that may help to stratify risk and make individualized decisions.